Shared Strategies for Behavioral Switching: Understanding How Locomotor Patterns are Turned on and Off - Mesce, Karen A.; Pierce-Shimomura, Jonathan T. (Frontiers in Behavioral Neuroscience, 2010)
Animals frequently switch from one behavior to another, often to meet the demands of their changing environment or internal state. What factors control these behavioral switches and the selection of what to do or what not to do? To address these issues, we will focus on the locomotor behaviors of two distantly related “worms,” the medicinal leech Hirudo verbana (clade Lophotrochozoa) and the nematode Caenorhabditis elegans (clade Ecdysozoa). Although the neural architecture and body morphology of these organisms are quite distinct, they appear to switch between different forms of locomotion by using similar strategies of decision-making. For example, information that distinguishes between liquid and more solid environments dictates whether an animal swims or crawls. In the leech, dopamine biases locomotor neural networks so that crawling is turned on and swimming is turned off. In C. elegans, dopamine may also promote crawling, a form of locomotion that has gained new attention.